Genome-Wide Association Analysis of Sasang Constitution in the Korean Population - Kim, Bu-Yeo (Mary Ann Liebert, Inc., 2012)
OBJECTIVES: Sasang constitutional medicine is a traditional Korean medicine in which an individual is classified into one of four types of constitution: Taeum (TE), Soeum (SE) Soyang (SY), and Taeyang (TY). These constitution types are determined with biologic and physiologic characteristics, so it has been assumed that genetic factors are associated with each constitution type. Identifying the genetic elements underlying each constitution is necessary for the elucidation of the molecular mechanism of Sasang constitutional medicine. DESIGN: A total of 341,998 genetic loci across the whole genome were genotyped for 1222 subjects of defined constitution type. The genetic loci associated with each constitution type were identified and the functional connectivity of genes within these loci was analyzed using statistical text mining. RESULTS: From the difference in allele frequencies between constitution types, significant genetic loci associated with each type were identified. Chromosomes 3q27.3 (rs10937331, p=2.71×10(−6)), 15q22.2 (rs7180547, p=1.58×10(−6)), and 14q22.3 (rs12431592, p=1.31×10(−6)) were most significantly associated with TE, SE, and SY constitution types, respectively. From the functional relationship analysis using all loci with a p-value≤10(−4), genes associated with each constitution type were identified. Fifteen (15) genes, including GPM6A, SYT4, and GRIK1, were significantly associated with the TE constitution type (p<0.05); 12 genes, including DRGX and AKAP11, were significantly associated with the SE constitution type (p<0.05); and 17 genes, including ZFP42, CDH22, ALDH1A2, OTX2, and EN2, were significantly associated with the SY constitution type (p<0.05). CONCLUSIONS: Genetic loci and genes associated with Sasang constitution types were systematically identified from a genome-wide association study using a large number of subjects.